BLASPHEMY ACCORDING TO THE ITE LAW AND ISLAMIC LAW: AN EXAMINATION OF THE MIRZA ALFATH CASE, INDONESIA - Khairani Khairani; Chairul Fahmi; Aiyyub Sabar (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2018)
This research is about a case of insulting Islam committed by Malikussaleh University Faculty of Law Lecturer, Lhokseumawe Mirza Alfath who insulted Islam via the Internet. Based on the clarification of Mirza Al-Fath's statement, a lecturer at Malikussaleh University in the Lhokseumawe Police Chief's Hall, the Lhokseumawe City Ulema Consultative Assembly (MPU) concluded that Mirza Al-Fath's statements in the text, based on the criteria of the Aceh MPU Fatwa Number 4 of 2007, were heretical. Therefore, the researcher sees the case as a phenomenon of blasphemy in Lhokseumawe City. The researcher tried to see the case from the legal perspective of the ITE Law and Islamic Law how the sanctions given to Mirza Al-Fath. The method used in this research is field research method through normative approach. Research is conducted on regulations and legal materials. The purpose of this research is to further examine the problems that occur and how sanctions are given and see the extent of the legal status of the ITE Law and Islamic Law. The results of this study found that the basic criteria for blasphemy by Mirza Al-Fath is the emergence of a sense of hatred or hostility of individuals and/or certain community groups based on ethnicity, religion, race, and intergroup (SARA). Consideration of the ITE Law in regulating sanctions for perpetrators of blasphemy through social networks can be requested if the perpetrator is insafaf. Blasphemy is regulated in Article 28 paragraph (2) of Law Number 11/2008 on Electronic Information and Transactions. While the criminal provisions are regulated in article 45 paragraph (2) of Law Number 11 of 2008 concerning Electronic Information and Transactions. Meanwhile, according to Islamic law that everyone who harasses the values of sharia must be punished with death or recantation. The sanction given by Malikussaleh University is honourable dismissal as a lecturer.